Alex Delaware: Devils Waltz - Book 7 (New York : Bantam, 1993)
Dr. Alex Delaware goes to Western Pediatrics Hospital to help treat the mysterious illness of a child and gets involved with hospital politics and murder.
Keywords: Delaware, Alex (Fictitious character) -- Fiction; Child psychologists -- California; Los Angeles; Fiction; Sturgis, Milo (Fictitious character) -- Fiction; Police -- California; Los Angeles; Fiction; Child abuse -- Fiction; Los Angeles (Calif.) -- Fiction; Detective and mystery stories; Medical novels